Diversity of Nontuberculoid Mycobacterium Species in Biofilms of Urban and Semiurban Drinking Water Distribution Systems - September, S. M. (American Society for Microbiology, 2004)
Nontuberculous mycobacteria (NTM) are ubiquitous and have been isolated from a variety of environmental sources, including water. Various NTM were isolated from biofilms in drinking water distribution systems in two urban and two semiurban areas in South Africa. Most of the isolates belonged to opportunistic pathogenic species of the NTM group, but none belonged to the Mycobacterium avium complex.